Putri Yefta, Korban Perang Sang Ayah: Menafsir Ulang Hakim-Hakim 11:29-40 - Agustina Raplina Samosir (STT Iman Jakarta, 2022)
The interpretation of Jephthah's vows is divided into two major views: pro-life (Jephthah did not sacrifice his daughter as a burnt sacrifice) and counter-life (Jephthah sacrificed his daughter as a burnt sacrifice). These two views have their own arguments. The interpretation of pro-life holds that Jehovah was so opposed to human sacrifice that Jephthah offered his daughter as a man of God in the Temple. On the contrary, the counterlife interpretation considers evidence primarily of the naming of Jephthah's daughter among the daughters of Israel that Jephthah offered his daughter as a burnt sacrifice. According to the author, many interpretations of pro-life ignore the evidence of the sacrifice of Jephthah's daughter. On the other hand, the interpretation of counterlife needs to look at other evidence in favor. The narrative interpretation of Judges 11:29-40 will show that Jephthah's innocent daughter was the victim of her father's war. This research aims to find that Jephthah offered his daughter as a burnt sacrifice because Jephthah had to be responsible for fulfilling his vows. Besides, there was no voice from heaven to prevent his daughter's sacrifice or offer a substitute. Jephthah's daughter fell victim to her father's war. From the beginning, Jephthah risked his entire home to become a victim of the postwar war. Jephthah offered his daughter a burnt sacrifice because Jephthah had to be responsible for fulfilling his vows. There was no voice from heaven to prevent his daughter's sacrifice or offer a substitute. AbstrakTafsiran atas nazar Yefta terbagi menjadi dua pandangan besar yakni prokehidupan (Yefta tidak mengorbankan anak perempuannya sebagai kurban bakaran) dan kontrakehidupan (Yefta mengorbankan anak perempuannya sebagai kurban bakaran). Dua pandangan ini memiliki argumentasi masing-masing. Tafsiran prokehidupan berpandangan bahwa Yahwe sangat menentang kurban manusia sehingga Yefta mempersembahkan anak perempuannya sebagai abdi Allah di Bait Suci. Sementara itu, tafsiran kontrakehidupan mempertimbangkan bukti terutama pengenangan nama anak perempuan Yefta di antara putri-putri Israel bahwa Yefta mempersembahkan anak perempuannya sebagai kurban bakaran. Menurut penulis, tafsiran prokehidupan banyak mengabaikan bukti pengurbanan anak perempuan Yefta. Di sisi lain, tafsiran kontrakehidupan perlu melihat bukti lain yang mendukung. Tafsir ulang atas Hakim-hakim 11:29-40 akan memperlihatkan bahwa anak perempuan Yefta yang tidak bersalah menjadi korban perang ayahnya. Sejak awal Yefta merisikokan seisi rumahnya untuk menjadi korban perang pascaperang. Yefta mempersembahkan anak perempuannya sebagai kurban bakaran sebab Yefta mesti bertanggung jawab untuk memenuhi nazarnya dan tidak ada suara dari surga yang mencegah pengurbanan anak perempuannya tersebut atau menawarkan kurban pengganti.